Screening and identification of muscle pericyte selective markers - Jingsong Ruan; Minkyung Kang; Rong Wang; Wanling Xuan; Feng Cheng; Yao Yao (Scientific Reports)
Abstract Pericytes, which share markers with smooth muscle cells (SMCs), are heterogenous cells. Pericytes in the brain and skeletal muscle have different embryonic origins, representing distinct subpopulations. One challenge in the field is that there are no subpopulation-specific pericyte markers. Here, we compared the transcriptomes of muscle pericytes and SMCs, and identified 741 muscle pericyte-enriched genes and 564 muscle SMC-enriched genes. Gene ontology analysis uncovered distinct biological processes and molecular functions in muscle pericytes and SMCs. Interestingly, the Venn diagram revealed only one gene shared by brain and muscle pericytes, suggesting that they are indeed distinct subpopulations with different transcriptional profiles. We further validated that GSN co-localized with PDGFRβ+SMA− cells in small and large blood vessels but not PDGFRβ+SMA+ cells, indicating that GSN predominantly marks pericytes and fibroblasts rather than SMCs in skeletal muscle. Negligible levels of GSN were detected in the brain. These findings indicate that GSN may serve as a selective marker for muscle pericytes.